Obstacles to electronic field training from the perspective of social work students at Princess Rahma University College - lsaideh, jehad (Journal of Social Sciences and Humanities, 2025)
The study aimed to identify the challenges confronted field training in the social works division while reliant on on-line learning. The study used a comprehensive social survey method while its sample was all the 76 students listed on filed training on first semester of the year 2022-2023. The study results showed that the most prominent challenges confronted students field training on e-Learning refer to students themselves are the struggling of adhering to training times besides the inability to build face-to-face relationships with establishments connected to social works. As for the most prominent challenges facing field training in on-line learning due to the use of e-learning technology is the Internet frequent cutting-off followed by the lack of on-line learning applications. results also showed that the most facing field training in on-line learning due to training outcomes are the incapacity of expected skills beside the lack the opportunity to apply social service methodologies such as case studies,The study rustles exposed that there are no statistically significant differences in the challenges confronted field training students according to field study specialization, while there are statistically significant differences in the challenges facing students according to field training.The study recommended the need to combine traditional education and on-line learning in training social work students to achieve the training objectives.